MODIFICATION OF CLARK AND WRIGHT VEHICLE ROUTING PROBLEM ALGORYTHM - Nefiodov, N.; Нефедов, Н. А.; Нефьодов, М. А. (Харьковский национальный автомобильно-дорожный университет, 2017)
Based on the analysis of shortcomings of existing algorithms for solving the problem conveying the developed method modification of the method of Clarke and Wright is based on the dynamic transformation of the payoff matrix. To verify the effectiveness of the modified algorithm, the data of real beneficiaries of a batch of goods in the central part of Kharkiv was used as a test example. The results of the comparison showed that the mileage of vehicles on routes built using the modified algorithm is by about 0,1–3,8 % less.
МОДИФИКАЦИЯ АЛГОРИТМА КЛАРКА И РАЙТА МАРШРУТИЗАЦИИ ПЕРЕВОЗОК ПАРТИОННЫХ ГРУЗОВ
МОДИФІКАЦІЯ АЛГОРИТМУ КЛАРКА І РАЙТА МАРШРУТИЗАЦІЇ ПЕРЕВЕЗЕНЬ ГУРТОВИХ ВАНТАЖІВ
Keywords: customer transport service; delivery route; route time; VRP; dynamic savings matrix; routes merging; savings account means; vehicle carrying capacity; партионные грузы; задача развозки; матрица выигрышей; слияние маршрутов; вместимость автомобиля; способ расчета выигрышей; гуртові вантажі; завдання розвезення; матриця виграшів; злиття маршрутів; 656.073.52